COVID-19 PANDEMIC AND CONSTITUTIONALISM IN THE REPUBLIC OF NORTH MACEDONIA - Treneska Deskoska, Renata (International Association of Constitutional Law, 2022)
COVID-19 has posed unprecedented challenge not only for health system, but also for legal systems all over the world. This paper analyzes the legal challenges, North Macedonia has been facing because of COVID-19 pandemic. In 2020, when the pandemic started, the Parliament of North Macedonia was dissolved and pre-term elections were called. In order to postpone the elections and to give the Government possibility to act efficiently in situation of dissolved Parliament, the President of the Republic proclaimed state of emergency. The interim Government was challenged to respond efficiently to the pandemic and its consequences, by using minimal restrictions of human rights. The paper analyzes the issue of balancing the values of constitutionalism with the need of efficient measures to deal with the pandemic in North Macedonia. The role of the constitutional arrangements in responding to the COVID-19 crisis are also analyzed. The importance of the constitutional norms during the state of emergency in North Macedonia was big, because the country did not have the Law on state of emergency, so the constitutional norms were only legal norms that regulated the situation in which the country was for a first time since its independence. The paper also assesses the adopted measures by the Government and their influence on the rule of law and democratic principles in the country. The Constitutional court was very active during the state of emergency deciding on the constitutionality of almost all decrees with the force of law which were adopted by the Government. The paper also analyzes the role of the Constitutional Court of the Republic of North Macedonia as guardian of the Constitution during the state of emergency.
Keywords: constitution, constitutionalism, COVID-19, North Macedonia